Playing American Open-World Videogames and the Reproduction of American Culture - Schoppmeier, Sören (Video Games and the Humanities, 2023)
Tracing a practice called "playing American" through the stages of videogame development, gameplay, and reception, this book delineates how aspects of American culture are reproduced transnationally through popular open-world videogames. Case studies of the Grand Theft Auto, Watch Dogs, and Red Dead Redemption franchises highlight different figurations of this phenomenon.